Reframing “Hadith Rejection”: Epistemological Reduction and Methodological Diversity in Contemporary Hadith Studies - Abbas Langaji; M. Ilham; Muhammad Irfan Hasanuddin (UIN Sunan Kalijaga Yogyakarta, 2026)
This study seeks to clarify the labeling of hadith rejection by distinguishing between ontological rejection and methodological criticism in assessing the authority of hadith. Employing a qualitative approach grounded in library research and critical discourse analysis, it examines the intellectual debates surrounding key figures commonly associated with hadith rejection, including classical scholars, modern reformists, and Western Orientalists. The findings reveal that the label “hadith rejecter” is not a fixed epistemological category but rather a discursive construct shaped by methodological differences and ideological biases. Many scholars labeled as rejecters do not deny the Prophet’s authority; instead, they propose alternative criteria for the authenticity and interpretation of hadith. This study argues that the prevalent use of this term results in an epistemological oversimplification that obscures the diversity of approaches within hadith scholarship. By distinguishing among three categories, ontological rejection, methodological criticism, and epistemological differences, this research offers a more nuanced analytical framework. Ultimately, the study contributes to a more balanced and dialogical understanding of hadith studies, reduces polarization, and promotes a more inclusive interpretation of intellectual diversity within Islamic thought.